UMPSA Vice-Chancellor launches Student Services Initiative and visits Student Residences - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 16 January 2025 – The Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dr. Yatimah Alias, today launched the Student Services Initiative by the Student Affairs and Alumni Department (JHEPA).